O discurso sobre a precariedade em Luiz Ruffato e Arlindo Gonçalves - José Leonardo Tonus (Estudos de Literatura Brasileira Contemporânea)
The discourse about precariousness in Luiz Ruffato and Arlindo Gonçalves José José Leonardo Tonus This study aims to analyze how, in the novels Eles eram muitos cavalos by Luiz Ruffato and Desonrados e outros contos by Arlindo Gonçalves, the literary device of landscape contributes to the emergence of a discourse about precariousness. If the landscape occupies, in these texts, a central place in thinking about social degrada- tion, it is not limited to a nostalgic record of a world in ruins. In both novels, the device of landcape contibutes both to the triggering element of artistic creation as much as its failure. Like our fragmented perception of a degraded urban universe, here the landscape indicates our relationship with the alter territory.